Plasmon Enhanced Fluorescence and Raman Scattering by [Au-Ag Alloy NP Cluster]@SiO2 Core-Shell Nanostructure - Zhang, Chengyun; Zhang, Tingting; Zhang, Zhenglong; Zheng, Hairong (Frontiers in Chemistry, 2019)
Silica-shell coated noble metal nanoparticles have shown a good performance in surface enhanced fluorescence and Raman scattering. However, silica-shell coated single noble nanoparticle cannot effectively enhance the optical signal due to the relative weak near-field enhancement. In this paper, [Au-Ag alloy NP cluster]@SiO2 core-shell nanostructure is employed to achieve the effective electric field enhancement. With the specific structure, simultaneous Raman scattering and fluorescence emission enhancement is obtained, and the enhancement comparison of fluorescence emission with Raman scattering in different type agglomeration of metal NPs is investigated in-situ. With different thickness of SiO2 shell, the optimized Raman and fluorescence enhancement systems are obtained, respectively, and corresponding study of power dependence are investigated in detail. The selectively enhanced Raman and fluorescence can be realized via controlling the shell thickness and laser power. Our work provides a non-polarization dependent [metal NP cluster]@SiO2 system, which may have a promising application in portable chemical and biochemistry detecting.